Evaluasi Alat Tangkap Ikan Pelagis yang Ramah Lingkungan di Perairan Maluku dengan Menggunakan Prinsip CCRF (Code of Conduct for Responsible Fisheries) - Alberth CH Nanlohy (Fakultas Peternakan Universitas Kristen Palangka Raya, 2013)
Code of Conduct for Responsible Fisheries (CCRF) utilized as guidance for fishery activity in having responsibility. This technical manual will give equipment required to national and international effort to guarantee sustainability of aquatic resources and fishery activity. Fishing gear tonda was taking first ranking with score 8,38 based on scoring criteria of sustainable fishing gear, second ranking was huhate with score 7,88, and third ranking was surface gill net with score 7,22. Fishing gear tonda was to fulfill most all conditions required as sustainable fishing gear, includes as : friendliness technology, number of hauls doesn't exceed TAC, profits, low investment, usage of low BBM, pursuant to applicable law, and environmental friendliness aspect like: high selectivity, not destructive to habitat, haul with quality height, doesn't endanger for fisherman, product doesn't danger for consumer, minimum by-catch and discard, doesn't catch nearly extinction species, minimum impact to biodiversity, and acceptable to social communities.